2019
DOI: 10.1063/1.5079931
|View full text |Cite
|
Sign up to set email alerts
|

On the reduction and rectification of thermal conduction using phononic crystals with pacman-shaped holes

Abstract: We measure the thermal conductivity of silicon phononic crystals with asymmetric holes at room and liquid helium temperatures and study the effect of thermal rectification, phonon boundary scattering, neck transmission, and hole positioning. Also, we compare the influence of asymmetric holes on thermal conductivity reduction with the one of conventional circular holes. This reduction is almost 40% larger in the case of pacman shaped holes as compared with circular ones for the same parameters of phononic cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 21 publications
2
21
0
Order By: Relevance
“…The carrier scattering becomes strongly energy dependent, which increases the Seebeck coefficient. Another nano-feature that has been widely explored are nanopores, which drastically reduce thermal conductivity [26,28,141,142,143,144,145,146,147,148,149]. Porosity could lead to an increase in the Seebeck coefficient due to the increase of the entropy per charge carrier due to energy filtering at the pore boundaries, but as we will show later on, this improvement is not significant.…”
Section: Nanostructuring: Materials Methods and State-of-the-artmentioning
confidence: 99%
“…The carrier scattering becomes strongly energy dependent, which increases the Seebeck coefficient. Another nano-feature that has been widely explored are nanopores, which drastically reduce thermal conductivity [26,28,141,142,143,144,145,146,147,148,149]. Porosity could lead to an increase in the Seebeck coefficient due to the increase of the entropy per charge carrier due to energy filtering at the pore boundaries, but as we will show later on, this improvement is not significant.…”
Section: Nanostructuring: Materials Methods and State-of-the-artmentioning
confidence: 99%
“…Nanophononics and nanomechanics deal with vibrations in solids where the typical frequencies are in the range spanning from few GHz up to THz. [1][2][3][4][5][6][7][8][9][10][11][12] These frequencies have associated wavelengths in the 1-100 nm range, making them interesting for high-resolution acoustic imaging and sensing applications. Ultrasound imaging in the kHz-MHz has revolutionized medical applications; a similar impact can be predicted for nanoacoustic waves for non-destructive testing at the nanoscale.…”
Section: Introductionmentioning
confidence: 99%
“…Rectification values of up to 350% were theoretically predicted in graphene nanoribbons [22], while experiments showed that graphene junctions could provide even higher values of up to 800% rectification [12]. In the more technologically placed silicon, theoretical studies suggest that geometrically asymmetric structures can enhance thermal rectification effects [14][15][16][17][18][19], verified by some experimental works as well [10,15,23]. Rectification is achieved when the structure is separated into regions in which the mean-free-path (MFP) is controlled by two mechanismsthe temperature-dependent Umklapp scattering, and a mechanism much less temperature dependent such as boundary scattering.…”
Section: Introductionmentioning
confidence: 85%